1983
DOI: 10.1002/ajmg.1320150119
|View full text |Cite
|
Sign up to set email alerts
|

Cebocephaly‐holoprosencephaly in a newborn girl with a terminal 7q deletion [46,XX,del(7)(pter→q32:)]

Abstract: Cytogenetic study of a day-old infant showed a terminal del(7q): 46,XX,del(7)(pter leads to q32:). This infant had cebocephaly with holoprosencephaly. These clinical findings are atypical for the 7q - syndrome, in which patients usually have growth and mental retardation with few facial abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

1984
1984
1998
1998

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 9 publications
0
13
0
1
Order By: Relevance
“…This may be due to ascertainment bias. Included in this review of cytogenetic abnormalities in holoprosencephaly are reports with dup( l)(ql2) [Gardner et al, 1974, cases FQ58l and 10581, dup( l)(q32-+qter) and de1(7)(q34-+qter) [Schinzel, 1984;, three related newborn infants], dup(l)(q42--.qter) and del( 18p) [Liberfarb et al, 19791, de1(2)(p21-+p22.1) (present case), dup(3)(p21-+pter) [Van Regemorter et al, 1983;Gillerot et al, 1987;Kurtzman et al, 19871, dup(3)(p21-+pter) and del(l8p) [Buchinger et al, 19811, dup(3)(p23-pter) [Gimelli et al, 19851, dup(3)(p25-pter) [Martin and Steinberg, 19831, del(5)(pl5-+pter) and dup( 13)(q22+qter) [Yanagisawa et al, 1978 1, d e l ( 5 ) ( p l 5 -+ p t e r ) and dup(5)(q35-qter) [Schroeder et al, 19861, r(6) [Peeden et al, 19821, dup(6)(p21dpter) [Pearson et al, 1979;Smith and Pettersen, 19851, dup(6) (q21-qter), [Neu et al, 19811, de1 (7)(q21+q31) [Ayraud et al, 19761, de1 (7)(q32-+qter) [Friedrich et al, 1979;Schwartz et al, 1983;McMorrow et al, 19871, de1(7)(q34-qter] and dup(l8)(q21+qter) [Smart et al, 19861, dup(ll)(q211+qter) [Pihko et al, 19811, tetrasomy (12p) [Steinbach and Rehder, 19871, r(13) [review by Niebuhr and Ottosen, 19731, del(l3q) and dup(l3q) [review by Niebuhr, 1977;Wilson et al, 19871, dup(l4)(pter--.q24) [Cottrall et al,198 11, [Buckton and Barr, 19811, r(18) [Dumars et al, 1970;Yanoff et al, 1970 Cohen et al, 19721, i(18q) [Froster-Iskenius et al, 1984;Spinner, personal communication], del( 18p), and trisomy 18 [review by Schinzel, 19831, trisomy 20 [Becker and ...…”
Section: Discussionmentioning
confidence: 98%
“…This may be due to ascertainment bias. Included in this review of cytogenetic abnormalities in holoprosencephaly are reports with dup( l)(ql2) [Gardner et al, 1974, cases FQ58l and 10581, dup( l)(q32-+qter) and de1(7)(q34-+qter) [Schinzel, 1984;, three related newborn infants], dup(l)(q42--.qter) and del( 18p) [Liberfarb et al, 19791, de1(2)(p21-+p22.1) (present case), dup(3)(p21-+pter) [Van Regemorter et al, 1983;Gillerot et al, 1987;Kurtzman et al, 19871, dup(3)(p21-+pter) and del(l8p) [Buchinger et al, 19811, dup(3)(p23-pter) [Gimelli et al, 19851, dup(3)(p25-pter) [Martin and Steinberg, 19831, del(5)(pl5-+pter) and dup( 13)(q22+qter) [Yanagisawa et al, 1978 1, d e l ( 5 ) ( p l 5 -+ p t e r ) and dup(5)(q35-qter) [Schroeder et al, 19861, r(6) [Peeden et al, 19821, dup(6)(p21dpter) [Pearson et al, 1979;Smith and Pettersen, 19851, dup(6) (q21-qter), [Neu et al, 19811, de1 (7)(q21+q31) [Ayraud et al, 19761, de1 (7)(q32-+qter) [Friedrich et al, 1979;Schwartz et al, 1983;McMorrow et al, 19871, de1(7)(q34-qter] and dup(l8)(q21+qter) [Smart et al, 19861, dup(ll)(q211+qter) [Pihko et al, 19811, tetrasomy (12p) [Steinbach and Rehder, 19871, r(13) [review by Niebuhr and Ottosen, 19731, del(l3q) and dup(l3q) [review by Niebuhr, 1977;Wilson et al, 19871, dup(l4)(pter--.q24) [Cottrall et al,198 11, [Buckton and Barr, 19811, r(18) [Dumars et al, 1970;Yanoff et al, 1970 Cohen et al, 19721, i(18q) [Froster-Iskenius et al, 1984;Spinner, personal communication], del( 18p), and trisomy 18 [review by Schinzel, 19831, trisomy 20 [Becker and ...…”
Section: Discussionmentioning
confidence: 98%
“…Several associated facial abnormalities have been described, including cyclopia (with a proboscis above the single orbit), premaxillary agenesis with midline or bilateral cleft lip and palate, ocular hypotelorism with or without a proboscis (ethmocephalus), and ocular hypotelorism with a flat, single-nostril nose (cebocephalus). 1 .3 The antenatal sonographic diagnosis of holoprosencephaly has been described multiple times.u 5 Shinzel et al described two cases of cebocephaly in which a sagittal scan of the fetal face showed hypoplasia of the nose in one of the cebocephalic fetuses. :z In our case, coronal scanning of the fetal face enabled us to visualize J Ultrasound Med 7;395-398, 1988 and correctly characterize the hypotelorism and small proboscis with a single nostril.…”
Section: Discussionmentioning
confidence: 99%
“…Although HPE in terminal 7q deletion had been reported by F'riedrich et al [19791, it was considered as an exception. More recently, the association of terminal 7q deletion with prosencephalic anomalies has been substantiated by reports of Schwartz et al [1983] and McMorrow et al [1987] on infants with HPE and cebocephaly and de1(7)(pter-.q32:).…”
Section: Introductionmentioning
confidence: 94%